Effects of Hyperbaric Oxygen Preconditioning on Doxorubicin Cardiorespiratory Toxicity - Vivian Doerr; Ryan N. Montalvo; Branden L. Nguyen; Franccesco P. Boeno; Michael D. Sunshine; Victoria E. Bindi; David D. Fuller; Ashley J. Smuder (MDPI AG, 2022)
Cardiorespiratory dysfunction resulting from doxorubicin (DOX) chemotherapy treatment is a debilitating condition affecting cancer patient outcomes and quality of life. DOX treatment promotes cardiac and respiratory muscle pathology due to enhanced reactive oxygen species (ROS) production, mitochondrial dysfunction and impaired muscle contractility. In contrast, hyperbaric oxygen (HBO) therapy is considered a controlled oxidative stress that can evoke a substantial and sustained increase in muscle antioxidant expression. This HBO-induced increase in antioxidant capacity has the potential to improve cardiac and respiratory (i.e., diaphragm) muscle redox balance, preserving mitochondrial function and preventing muscle dysfunction. Therefore, we determined whether HBO therapy prior to DOX treatment is sufficient to enhance muscle antioxidant expression and preserve muscle redox balance and cardiorespiratory muscle function. To test this, adult female Sprague Dawley rats received HBO therapy (2 or 3 atmospheres absolute (ATA), 100% O2, 1 h/day) for 5 consecutive days prior to acute DOX treatment (20 mg/kg i.p.). Our data demonstrate that 3 ATA HBO elicits a greater antioxidant response compared to 2 ATA HBO. However, these effects did not correspond with beneficial adaptations to cardiac systolic and diastolic function or diaphragm muscle force production in DOX treated rats. These findings suggest that modulating muscle antioxidant expression with HBO therapy is not sufficient to prevent DOX-induced cardiorespiratory dysfunction.